Perspektif Kelembagaan, Tekanan Eksternal, dan Pengungkapan Tanggung Jawab Sosial Perusahaan - Teddy Jurnali; Susanti Susanti (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
Corporate Social Responsibility (CSR) is a corporate responsibility towards the social or the surrounding environment as a result of company operations. In Indonesia, there are many factors that influence a company in disclosing CSR such as government intervention (Laws, Government Regulations and Regional Regulations), external corporate pressure on CSR (foreign subsidiaries and company scale), as well as institutional perspectives (industry sensitivity and CSR promoting institutions). This study examines the institutional perspective of CSR reporting among listed companies in Indonesia. The purpose of this paper is to identify the influence of sensitivity industries; the presence of CSR promoting institutions; subsidiaries of MNC’s and business size and explore the managerial perceptions on CSR reporting. This research extends the existing literature on the debate over accountability, regulation, international standards, sustainability, and the influence or otherwise of other stakeholders by exploring organisational and external institutional drivers of CSR reporting in developing countries. This research was conducted with quantitative data and linear regression methods with 1,730 data or the same as 346 companies. The result showed that sensitivity industries, subsidiaries of MNC’s and business size have a significant effect on CSR disclosure, while CSR promoting institutions was not able to affect CSR disclosure significantly. This study helps to understand how institutional perspectives as well as company external pressures can influence CSR disclosure in Indonesia.